TAJOO ROOBAA (Arsi Journal of Science and Innovation, 2025)
ABSTRACTOromo of Kush, largest communities in East Africa have experienced indigenous socio-economic and political life and livelihood aspects under the Gadaa system- the pioneer indigenous classical African Civilization system. Irressaa is –Thanks Giving to Waaqaa(Oromoos God). This Thanks given ceremony has practices twice a year (Irressaa Tullu and Irressaa Melka)- at the end of rainy season and the beginning of rainy Season). Irre(ch)ssaa is performed at different parts of Oromia, with varies colorful,rutual,spiritual and performance. Irressaa Hor-Sadee(Bushooftu) is well known and celebrated with colorful and mass participation. The study was undertaken in Arsi Zone, Oromia national regional state, 2021/222 G.C. The study employed ethnographic qualitative methods in which the data were collected through participant observation, interview, and secondary sources. Open-ended/semi-structured questionnaires and indigenous documentation approaches were administered accordingly. The study area was limited to Utaa Wayyuu of Arsi Oromoo largely resides in Arsi Zone(Zuway Dugdaa, Munessa and Lemu Bilbilloo woredas) and East Shoa Zone(Adami Tullu Jido Kombolcha). This study revealed that Arsi Oromoo have celebrated Irressaa Melkaa (Denbal Lake), known as Tajoo Roobaa. Tajoo Roobaa largely known and practiced among Utaa Waayyuu of Arsi Oromo. Tajoo Roobaa is ritual cultural practices that performed in Hinikkaa-Ayyaanaa Waaqaa- the first day, new year of Oromo calendar under the rule Shanoo Shanecha(Gadaa Council- representative five Gadaa class). In the Absence of Gadaa rule, there is no Tajoo Roobaa celebration (practices), because it is one element that passed through Gada system. Tajoo Roobaa – Irreessaa of Arsii is celebrated by clans leaders and members, all Arsii Gurrachaa(Oromoo) in large under Gadaa administration. Therefore, Tajoo roobaa festivity and celebration is very significant in Irreechaa terms of rituals, spirituals, performances and material cultures. It is Oromoo indigenous universal philosophy of Thanks given and Praying for Their Waaqaa(Oromoos God). Tajoo ritual practices and performances give fundamental values for human and universal right- which is a pillar of Gada Values. Hence, it needs the concerning actors to focus and supports further studies to preserve and promote values, significances and socio-cultural values of Tajoo Roobaa for our generation and global communities in general.